Análise in silico do papel do receptor imune TREM-1 na infecção pelos Norovírus murino e humano - Colmenares, Mike Telemaco Contreras (2024)
In humans, Norovirus (NoV) is one of the main causes of acute diarrheal disease (ADD). Due to the limitations of NoV cultivation, some molecular aspects of its interaction with the host's immune system remain unknown. The triggering receptor expressed on myeloid cells 1 (TREM-1) is associated with the amplification of inflammatory responses and the progression of infections, including viral infections. Thus, we believe that TREM-1 may be involved in the NoV infection. Initially, we investigated the expression of Trem1 and the genes involved in its pathway, in transcriptomic data bank of public domain. In experimental infection with murine Norovirus (MNoV), the expression of Trem1 was increased. We also observed that there is a co-expression of Trem1 and genes involved in the pyroptosis pathway, when compared to those in the apoptosis pathway. The in silico protein-protein interactions were assessed by molecular docking simulations between the Ig-like domain of murine TREM-1 and the P domain of the MNoV VP1 protein. The murine TREM-1 recognized the conserved C´-D´ antigen that is present in the murine VP1. In this regard, and based on phylogenetic criteria, different structures of the VP1 protein of NoV GII.4 strains from different years (1987, 2010, 2012, 2014, 2016 and 2019) were modeled. We performed docking and molecular dynamics (MD) simulations to determine the in silico interaction between the VP1 protein of NoV GII.4 and the Iglike domain of human TREM-1. The DM simulations suggest that there is a basic interaction between human TREM-1 and the NoV VP1 protein, regardless of the year of isolation. Interestingly, we observed changes in the participation of the different complementarity determining regions (CDRs) of TREM-1 when interacting with the domains of the VP1 protein, highlighting the participation of CDR3. Our data strongly suggests the involvement of TREM-1 in the recognition of NoV and its participation in the physiopathology of ADD caused by NoV.